A Digital Tehcnology Innovation Financial Reporting Based Of Software Accurate Accounting System - Sri Hartati Sidauruk; Muhammad Saleh Rizkian; Hilda Elsera Br Sembiring (SEAN Institute, 2024)
The lack of expertise in using technology in the accounting process has led to the emergence of new problems, namely the difficulty of getting decent work for job seekers, there are various educational backgrounds, from high school graduates, vocational school graduates, to undergraduate graduates from various universities. This research aims to see whether the role of digital accounting based on the Accurate Accounting System is useful, appropriate and appropriate in presenting financial reports. The use of accurate has differences before and after using digital accounting and has advantages and disadvantages in presenting financial reports. This research is quantitative research, with samples taken using the total sampling method where the number of samples is the same as the population, with a total sample of 34 Gajah Mada Private Vocational Schools in Medan. Hypothesis testing in this research uses SPSS V26. The aim of this research is to increase Accurate Accounting System expertise in financial reporting technology innovation so that in the future Gajah Mada Medan Private Vocational School is able to compete in the industry 5.0 era.